PERLINDUNGAN HUKUM TERHADAP ANAK YATIM PIATU DI PANTI ASUHAN TUNAS HARAPAN SAMARINDA DI SAMARINDA - Awang Ramdani Wahyudin (Journal of Law ( Jurnal Ilmu Hukum ), 2013)
Abstract In the protection of children parents are obliged and responsible for , among others , caring and nurturing and educating children , in case parents do not execute this obligation especially in parenting , this task can be performed by an authorized agency for the orphanage which , like is governed by Article 27 of Law No. 23 of 2003 , " child care is first and foremost the duty and responsibility of parents within the family but for the sake of social order and for the benefit of the child, there are those who need melindunginya.1 one social institutions that organize child care is Tunas Harapan orphanage in samantha , Orphanage children are an Enterprise social Welfare Institutions that have a responsibility to provide social welfare services to neglected children , as well as doing sponsorship and poverty , providing a replacement service or child custody in meet the needs of physically, mentally and socially to foster care so as to obtain ample opportunity